Social and behaviour change intervention for scaling equitable access to rice and common beans quality seeds to women and young smallholder farmers in Butaleja District Eastern Uganda - Lengewa, Catherin; Mikhala, Audrine; Aura, Sylvester; Amuda, Alex; Yila, Jummai; Nchanji, Eileen; Bomuhangi, Allan (2024)
This report covers the period from November 2023 to February 2024. It is a report on activities implemented by the Centre for Behaviour Change and Communication (CBCC) under the Social and Behaviour Change Interventions for Scaling Equitable Access to Quality Seeds to the Women and Young Smallholder Farmers in Butaleja District, Eastern Uganda. The project is funded by the International Rice Research Institute (IRRI) under the Seed Equal initiative. This project will contribute to addressing the challenge of equitable access to climate-resilient, market-preferred, and nutritious varieties of beans and rice in Butaleja District, Eastern Uganda. Thus, contributing to Outcome 3: at least 30 women and youth (individuals/collectives) will establish seed production and marketing enterprises; women, youth, and disadvantaged socio-economic groups in 10 sites can access affordable, market-demanded, and producer-preferred high yielding, resilient variety seed and Outcome 1: at least 5 R&D organizations and private seed companies deploy gender intentional strategies to reach women seed users and producer.